Elucidation Of The Expression And Role Of Carotenogenic Genes In Astaxanthin Production In A Hyper-Producing Mutant Of Xanthophyllomyces Dendrorhous - Ang, Fong Sim (2018)
Astaxanthin is a red xanthophyll pigment which is commercially used in aquaculture as feed additive and in pharmaceutical industries due to its strong antioxidant properties. Synthetic astaxantin is limited by its properties, production requirements and also the strict regulations concerning the safety of synthetic chemicals as food additives. This has led to the alternative microbial production of natural astaxanthin. Xanthophyllomyces dendrorhous has desirable properties and commercial value as a dietary source of natural astaxanthin, but it has relatively low content of astaxanthin.